Technical Quality of Contemporary Endoscopic Sinus Surgery: An Assessment by Study of Anatomical Features Needing Attention at Revision Surgery - Nitish Kumar; Pedro Lanca Gomes; Michael J. Marino; Amar Miglani; Devyani Lal (Sinusitis)
Although technical causes of endoscopic sinus surgery (ESS) failure have long been reported, we were curious about the quality of contemporary sinus surgery. The electronic health database of Mayo Clinic, Arizona was scrutinized to identify adult patients with diffuse chronic rhinosinusitis (CRS) who underwent revision ESS between January 2019 and September 2023 with a history of bilateral full-house ESS. Anatomical features on preoperative radiology and intraoperative endoscopy were cataloged: residual uncinate tissue, maxillary antrostomy with a non-incorporated natural os, residual ethmoidal septations (three septations > 3 mm), and inadequate sphenoid osteotomy (os size < 6 mm). Sixty-nine subjects were identified. A deviated nasal septum was present in 53.6%. Residual uncinate tissue was noted in 50.7% of patients associated with missed natural maxillary os in 39.13% of antrostomies. An inadequate os diameter was noted in 63.8% of sphenoidotomies. Significant residual septations were seen in posterior ethmoidal cells in 66.7% and anterior ethmoidal cells in 62.3% of patients. Residual frontoethmoidal cells were noted in 72.4% of patients. Although the extent of ESS must be individualized, a high prevalence of features reflecting suboptimal surgery that could limit the success of ESS was identified. These findings merit further consideration for focused training during residency and continuous professional development activities.